Synthesis, and vitro Antimicrobial Studies of Metal-Nheterocyclic carbene complexes - Muhand Dohan Abid (Academia One, 2025)
This study explores the possible synergy between dapsone, a sulfone medication with wellestablished medicinal uses, and carbene chemistry. In order to create new compounds with increased biological activity, the study intends to investigate the reactivity of carbenes with dapsone and its derivatives. Using the in-situ deprotonation technique, silver(I) complexes were created by reacting imidazolium salts with Ag2O to produce derived structures in a good yield. Ag(I)-NHC complexes are used as transfer reagents to prepare corresponding Pd(II)-NHC through the transmetallation process. All prepared complexes were characterized using techniques NMR and FT-IR that gave close and accurate results. The results of dapsone and silver(I) palladium(II) complexes against bacterial activity were good. The complexes of Ag(I) and Pd(I) offered a useful action. Despite having less biological activity than the antibiotic ciprofloxacin.
Keywords: NHC complexes; Antimicrobial; Silver